OXA‐ and GES‐type β‐lactamases predominate in extensively drug‐resistant Acinetobacter baumannii isolates from a Turkish University Hospital. (19th August 2013) - Cicek, A. C.; Saral, A.; Iraz, M.; Ceylan, A.; Duzgun, A. O.; Peleg, A. Y.; Sandalli, C.; Cantón, R.
Abstract We determined the antibiotic susceptibility and genetic mechanisms of resistance in clinical strains of Acinetobacter baumannii from Istanbul, Turkey. A total of 101 clinical strains were collected between November 2011 and July 2012. Antimicrobial susceptibility was performed using the Vitek 2 Compact system and E‐test. Multiplex PCR was used for detecting blaOXA‐51‐like, blaOXA‐23‐like, blaOXA‐40‐like and blaOXA‐58‐like genes. ISAba1, blaIMP‐like, blaVIM‐like, blaGES, blaVEB, blaPER‐2, aac‐3‐Ia and aac‐6′‐Ib and NDM‐1 genes were detected by PCR and sequencing. By multiplex PCR, all strains were positive for blaOXA‐51, 79 strains carried blaOXA‐23 and one strain carried blaOXA‐40. blaOXA‐51 and blaOXA‐23 were found together in 79 strains. ISAba1 element was detected in 81 strains, and in all cases it was found upstream of blaOXA‐51. GES‐type carbapenemases were found in 24 strains (GES‐11 in 16 strains and GES‐22 in 8 strains) while blaPER‐2, blaVEB‐1, blaNDM‐1, blaIMP‐ and blaVIM‐type carbapenemases were not observed. Aminoglycoside modifying enzyme (aac‐3‐Ia and aac‐6′Ib) genes were detected in 13 and 15 strains, respectively. Ninety‐seven (96%) A. baumannii strains were defined as MDR and of these, 98% were extensively drug resistant (sensitive only to colistin). Colistin remains the only active compound against all clinical strains. As seen in other regions, OXA‐type carbapenemases, with or without an upstream ISAba1, predominate but GES‐type carbapenemases also appear to have a significant presence. REP‐PCR analysis was performed for molecular typing and all strains were collected into 12 different groups. To our knowledge, this is the first report of GES‐11 and OXA‐40 in A. baumannii from Turkey.